Integrating community health into primary care: two case studies from Barcelona's Raval neighborhood - Ortega, Francisco; Bilbeny de Fortuny, Beatriu; Albuixech-García, Rocío; Raya Tena, Antonia; Barceló-Prats, Josep; Djurdjevic, Marija (Frontiers in Public Health, 2025)
IntroductionThis study aims to generate evidence on healthcare practitioners' initiatives to integrate community health principles into primary care. Two case studies explore the co-design and co-development of tailored solutions to address the emerging health needs of vulnerable populations in the Raval neighborhood of Barcelona. The interventions aimed to improve access to healthcare services by establishing new care pathways adapted to the unique needs of migrant communities, while promoting inclusivity and equity in healthcare delivery.MethodAn action-research approach was used during interventions conducted from December 2021 to March 2023 in Barcelona. This participatory iterative method included qualitative research to understand barriers hindering healthcare access and delivery; co-design of tailored training programmes focusing on structural and intercultural competences for both community members and HC practitioners; suicide prevention trainings for Filipino community representatives and PC providers; implementation of a community-based suicide prevention initiative; and evaluation of its effectiveness. Convenience and judgemental sampling engaged key stakeholders and influential figures from the Raval neighborhood. Sampling methods and R&I techniques are detailed in Case study 1 and Case Study 2.ResultsCase Study 1 identified significant obstacles to healthcare access among immigrant populations, including linguistic, cultural, and discrimination-related barriers, stemming from inadequate administrative procedures and limited professional awareness of structural and social determinants of health. Case Study 2 highlighted the elevated suicide risk in Raval during the COVID-19 pandemic, leading to the co-design and implementation of suicide prevention training and the establishment of a sustainable, multi-stakeholder network of collaboration. Results from research and innovation activities are categorized in a table included in the text, with lessons learned discussed in the Discussion section.ConclusionsThe findings underscore the critical role of primary care in identifying community needs and adapting services to meet the requirements of vulnerable populations through innovative approaches recommended by WHO and Medicus Mundi. Insights gained from these grassroots, bottom-up initiatives -driven by healthcare practitioners and conducted mostly during their free time- have been translated into actionable recommendations for policy and practice.